Answer:
75 - 35y / 3 + 2y = -4
( 75 - 35y + 6y ) / 3 = -4 [ Taking LCM ]
( 75 - 29y ) / 3 = -4
75 - 29y = -12
29y = 75+12
29y = 87
y = 3
hope that helps ✌
Replace F(x) with y
y=x^3-10x^2+24x
To find the roots replace y with 0.
0=x^3-10x^2-24x
Rewrite the equation as
x^3-10x^2+24x=0
Factor the left side
x(x-6)(x-4)=0
The solution is a result of
x=0, x-6=0, and x-4=0
The answer is:
x=0, 6, 4
Hello !
cos (a+b) = cos a cos b - sin a sin b
sin (a+b) = sin a cos b + sin b cos a
cos (a+b+c) = cos (a+(b+c))
cos (a+b+c) = cos a cos (b+c) - sin a sin (b+c)
cos (a+b+c) = cos a (cos b cos c - sin b sin c) - sin a (sin b cos c + sin c cos b)
cos (a+b+c)=cos a cos b cos c - cos a sin b sin c - sin a sin b cos c - sin a cos b sin c
it has gone up 4 lines and left -2 making it go for a (4,-2)